DETECÇÃO DE GENES DE RESISTÊNCIA ANTIMICROBIANA EM CROMOSSOMOS E PLASMÍDEOS DE STAPHYLOCOCCUS SPP. - Neves, M.c. [UNESP]; Rossi, O.d. [UNESP]; Alves, E.c.c. [UNESP]; Lemos, M.v.f. [UNESP] (Instituto Biológico, 2022)
The main of the present study was analyze the use of a french press device to obtain genetic material from staphylococci and to detect genes involved with chromosomal and plasmid resistance to the following antimicrobial drugs: oxacillin, gentamicin, kanamycin and vancomycin. The agar disc diffusion method was conducted initially for 50 strains and the bacterial susceptibility was confirmed by means of PCR reactions. The results from the antibiogram method revealed high sensibility to gentamicin and kanamycin (4%) and oxacillin (8%). All strains were susceptible to vancomycin. The DNA from the bacteria was obtained by means of physical lyses using a french press device. The genes mecA and aph’3 – IIIa were detected on the staphylococci chromosome and the gene aac(6’)Ie + aph(2’’) was observed either in the chromosome and in the plasmid content of the staphylococci analyzed. Based on the obtained results one can conclude that the methodology used to extract the genomic genetic material using the french press device was efficient and allowed a simple method to detect by PCR and to locate by ultracentrifugation, the staphylococci antibiotic resistance genes.

Este trabalho teve por objetivo analisar o uso da prensa francesa para se adquirir material genético de estafilococos e detectar possíveis genes de resistência cromossomais e plasmidiais aos antimicrobianos oxacilina, gentamicina, canamicina e vancomicina. O método da difusão de discos em ágar foi realizado, inicialmente, para 50 linhagens de estafilococos e a susceptibilidade antimicrobiana foi confirmada por meio de Reação em Cadeia da Polimerase (PCR). Os resultados obtidos pelo antibiograma constataram alta susceptibilidade para gentamicina e canamicina (4%) e oxacilina (8%). Todas as linhagens foram susceptíveis à vancomicina. O DNA bacteriano foi obtido por lise física a partir da prensa francesa. Os genes mecA e aph3’IIIa foram detectados no cromossomo dos estafilococos e o gene aac(6’) Ie + aph (2) foi observado tanto no cromossomo como no plasmidio destas bactérias. Pelos resultados pode-se concluir que a metodologia utilizada para a extração de DNA genômico, por meio da prensa francesa, foi barata e eficiente, pois possibilitou a detecção por PCR e a localização, por ultracentrifugação, de genes de resistência em estafilococos.
DETECTION OF ANTIMICROBIAL RESISTANCE GENES ON THE CHROMOSOME AND PLASMIDS FROM STAPHYLOCOCCUS SPP
Keywords: Dairy cattle; aminoglycosides; mecA; PCR; ultracentrifugation; Rebanhos leiteiros; aminoglicosídeos; mecA; PCR; ultracentrifugação